Organizing talk in group speaking tests: learning from high-scoring students. (4th December 2020) - Stephenson, Michael; Hall, Graham
Abstract: This article investigates how group speaking test candidates manage group talk during assessed, time-limited tasks. Drawing on recorded and transcribed data, it explores how higher-scoring learners manage spoken assessment tasks through their talk, moving conversations on or slowing them down in order to perform and complete the tasks' requirements in a timely way. These data are contrasted with the ways in which lower-scoring test candidates attempt to organize and manage assessed group talk. While the data and findings from this particular study can be used to teach students about, and prepare them for, multi-person discussions and, more specifically, task-oriented and time-limited group speaking tests, we also suggest that our awareness-raising investigatory approach, if brought into the classroom, offers learners (and teachers) a way of uncovering some of what actually occurs during talk, illuminating the 'invisible rules' that guide how participants engage in and manage interaction.